К изучению иудейских древностей Херсонеса Таврического - Оверман, Э.; Макленнан, Р.; Золотарев, М.И. (Археологія, 1997)
В статье приводятся иудейские древности, обнаруженные в Херсонесе в последние годы. Спільна археологічна експедиція українсько-американського Причорноморського проекту з 1994 р. проводить дослідження у північному районі Херсонеса в Криму. Результатом цих робіт є відкриття під підвалинами середньовічної базиліки великої громадської будівлі римського часу, у західній частині якої було розміщено іудейську синагогу. Є всі підстави стверджувати, що знайдені тут ще 1950 р. фрески, які раніше вважалися приналежними до базиліки, у дійсності були внутрішнім декоративним оздобленням стін синагоги. Аналіз знайдених тут археологічних матеріалів дозволяє датувати пам’ятку першими століттями нашої ери. На деяких фрагментах фрески добре збереглись продряпані зверху розпису написи-графіті грецькою мовою й івритом. Написи івритом спираються на біблійний текст (Захарія, 3.2). На двох уламках фрески збереглося продряпане грецьке слово (Еνλογτα), що перекладається як «благословіння» чи «похвала». Цей термін звичайно вживається у свідченнях, що походять від грекомовних іудейських общин. Знахідка іудейських і грецьких написів одного рівня і в одному археологічному контексті є важливим свідоцтвом для розуміння того, що ці документи, хоч і виконані різними мовами, але, судячи за характером тексту, безсумнівно, належать представникам однієї іудейської общини. Розкопки Причорноморського проекту реально підтвердили наявність іудейської общини у такому багатонаціональному і впливовому місті як Херсонес. Релігійне застосування івриту було для невеликої іудейської общини Херсонеса своєрідним засобом збереження власної ментальності в середині грекомовного, але абсолютно поліетнічного міста киплячих конкуруючих пристрастей, яким був Херсонес у пізньоримський та ранньосередньовічний часи. The Black Sea Project archaeological excavations at Tauric Chersonesus, located on the outskirts of the modem city of Sevastopol, began in 1994 under the auspices of the Crimean Branch of the Institute of Archaeology of the National Academy of Science, the Chersonesus Museum Preserve, Macalester College, and the University of Puget Sound. The project has focused on the confirmation and analysis of a Jewish community in this ancient Greek city on the Crimean Peninsula dating from sometime in the Roman period. The project began in 1993 with the initial excavations conducted in the summer of 1994. The project is a collaborative venture between Ukrainian and American scholars and students. The research has focused on fieldwork in the area of the famous «1935" basilica first excavated by G. D. Belov. The Black Sea Project excavations have focused on the identification of a Jewish presence at Chersonesus. Archaeological excavations have been focused in the area of a fifth century basilica where it has been postulated an earlier public space beneath the basilica may reveal a Jewish presence at Chersonesus from the Roman period. However the project has not focused solely on excavations in the field. Important research has been carried on the archives of the Chersonesus Museum Preserve with respect to the question of the Jewish community at Roman Chersonesus under the leadership of Robert MacLennan. The presence of Hebrew writing at a Greek-speaking diaspora site is extremely rare. The Jewish community at Chersonesus has provided us with a small but important piece of material evidence from a middle to late Roman diaspora community from Crimea. The archaeological data from the excavations of the Black Sea Project has identified a Jewish presence in the diverse and influential city of Chersonesus, located in the midst of the Roman and Byzantine city, situated near a commercial district, apparently thriving — for a time — in this city of tremendous importance and influence in the Black Sea region. Some within this community, apparently so at home in the Crimea and Chersonesus in particular, had retained or cultivated a connection, or a memory, of the symbolic center of their own collective identity — Jerusalem. And they did so, among other ways surely, through the retention of a language long left in Palestine but which they still claimed as part of their own particular identity within a city of competing claims and identities.